Her brand of justice - Daniels, B. J. (Daniels, B. J. Colt brothers investigation., 2023)
Ansley Brookshire's search for her birth mother takes her from the gated estate where she grew up to Lonesome, Montana. This is where she meets Buck Crawford. Determined to help, the gorgeous rancher introduces her to Colt Brothers Investigations. But someone wants the secrets surrounding her adoption to stay buried--and they'll do anything to keep her from uncovering the truth...